Identidade e trabalho nos Folhetos de Cordel (1964 - 1985) - Leite, Lucas Santos Ribeiro (2024)
About the discussion of the present time about labor relations, migratory movements, communities that have settled in metropolis, asserting themselves and making use of their identity as a mechanism of resistance, and also, given the need to understand an extensive repertoire of Chapbook, within the established period (1964-1985), this research was developed. Research objectives: to analyze the construction of a worker identity, a narrative about stereotypes, ethnic discussions and labor issues, involving migrants, the poor and marginalized: brazilian labors from the countryside and the city; to problematize the contrast between social misery and the “economic miracle”, a nation’s political and ideological project, in poetry; and, to analyze the production of Chapbooks, the content of the works and the compositions of northeastern artists of the time, as forms of resistance through the struggles that accompany the history of Brazil. Therefore, the main objective of the thesis is a study of the identity of Brazilian laborsin literature and cultural circuits during the Military Dictatorship. We use a Chapbook, that belong to the Fatos Acontecidos genre, to understand the reality of the labors (represented group) and the poets themselves, who, in turn, belong to the same group they represent, to understand the issues addressed. In order to understand the problem and have a broader vision, it will be common to insert northeastern poetry of Brazil into cultural circuits, such as cinema and brazilian music